2012
DOI: 10.1038/cgt.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radiosensitivity of non-small-cell lung cancer (NSCLC) by adenovirus-mediated ING4 gene therapy

Abstract: Radiotherapy is the common treatment of choice for locally advanced lung cancer, but the radioresistance of lung cancer remains a significant therapeutic obstacle. We previously demonstrated that adenovirus-mediated inhibitor of growth 4 (ING4) tumor suppressor gene delivery (AdVING4) can chemosensitize human hepatocarcinoma cells to anticancer drug cisplatin (CDDP). However, its radiosensitizing effects in cancer therapy are largely elusive. In the present study, we investigated the therapeutic efficacy of Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
(71 reference statements)
0
27
0
Order By: Relevance
“…ING4 has been reported to enhance chemosensitivity to DNA-damage agents, such as doxorubicin or etoposide in human hepatocarcinoma cells (19,26). Our previous data also demonstrated that adenovirus-mediated (AdVING4) gene therapy sensitized human hepatocarcinoma cells to cisplatin (CDDP) and enhanced the radiosensitivity of non-small-cell lung cancer (19,25). However, reversal of its resistance in human cancers has not been reported.…”
Section: Adenovirus-mediated Ing4 Expression Reduces Multidrug Resistmentioning
confidence: 82%
See 4 more Smart Citations
“…ING4 has been reported to enhance chemosensitivity to DNA-damage agents, such as doxorubicin or etoposide in human hepatocarcinoma cells (19,26). Our previous data also demonstrated that adenovirus-mediated (AdVING4) gene therapy sensitized human hepatocarcinoma cells to cisplatin (CDDP) and enhanced the radiosensitivity of non-small-cell lung cancer (19,25). However, reversal of its resistance in human cancers has not been reported.…”
Section: Adenovirus-mediated Ing4 Expression Reduces Multidrug Resistmentioning
confidence: 82%
“…Moreover, restoration of ING4 expression was found to suppress tumor growth in a p53-dependent and p53-independent manner, induce tumor cell cycle arrest and apoptosis (13,(19)(20)(21), and inhibit tumor angiogenesis by repressing nuclear factor-κB and hypoxia-inducible factor-1α (22)(23)(24). ING4 protein can also enhance radiosensitivity and chemosensitivity in nonsmall-cell lung cancer and hepatocarcinoma cells (19,25). In the present study, we first successfully established the CDDPinduced MDR phenotype in a gastric carcinoma cell line for assessing the effects of the AdVING4 gene on the reversion of the MDR phenotype in gastric carcinoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations